雷切爾斯論安樂死: Rachels on Euthanasia - WONG, Kai-Yee (International Journal of Chinese & Comparative Philosophy of Medicine, 2001)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 發表於1975年的〈主動及被動安樂死〉，雖然已成為醫學倫理學的經典著作，但該文引起的爭議，迄今未息。作者雷切爾斯在文章中攻擊傳統見解裡認為「主動／被動安樂死之區分在道德本有意義」的觀點。他的主要論証方式是對（i）「殺人在道德主跟見死不救有分別」提出質疑。其後，雷切爾斯回應論者對其論証的批評時，更否定（ii）判斷行為的道德對錯時，意圖的好壞是相干的考慮」。〈主動及被動安樂死〉所引發的辯論中，論者的焦點往往是雷切爾斯在該文中提出來的論據。本文則還論及他對批評者的回應，嘗試剖析雷切爾斯後來為自己所作的辯護，從而評價他的整體立場。本文第二節將簡要地說明幾個基本概念。在第三節，筆者透過對有關論爭的交代去說明「意圖」、「主動安樂死」 及「被動安樂死」 三者在雷切爾斯對有關問題的論述中如何互相緊扣。第四節採用雷切爾斯壇用的「相同化例子証明法」 指出他對（i）和（ii）的看法不能同時成立。第五節則通過對「雙重後果原則」的討論去進一步分析雷切爾斯對（ii）的批評。第六節嘗試正面說明我們應怎樣看「意圖好壞」和「殺人／見死不救」的考慮在道德評價活動中的互動關係，並據之而評析雷切爾斯所用的論証方法的根本問題。 Twenty-six years on, the debate generated by James Rachels’ ’Active and Passive Euthanasia’ (1975), one of the most widely reprinted articles on euthanasia in bioethics, is still very much alive. The following policy statement cited and attacked by Rachels in the article has thus become familiar to many bioethicists: ’The intentional termination of the life of one human being by another - mercy killing - is contrary to that for which the medical profession stands and is contrary to the policy of the American Medical Association. The cessation of the employment of extraordinary means to prolong the life of the body when there is irrefutable evidence that biological death is imminent is the decision of the patient and/or his immediate family.’ This statement, Rachels claims, endorses the ’conventional doctrine’ that there is an important moral difference between active and passive euthanasia, i.e., that it is permissible, at least in some cases, to withhold treatment and allow a patient to die, but it is never permissible to take any direct action designed to kill the patient. Rachels’ major objection is that this doctrine rests on the mistaken idea that there is a moral difference between killing someone and letting someone die. While commentators on Rachels’ rejection of the distinction between active and passive euthanasia focus mainly on his arguments against the moral difference between killing and letting die as put forth in ’Active and Passive Euthanasia’, this paper aims to give an evaluation of Rachels’ overall position by examining also the way in which he defends his arguments in ’ More Impertinent Distinctions and a Defense of Active Euthanasia’, an article published in 1978. In this article, Rachels responds to the objection that his earlier arguments against the distinction between killing and letting die failed to take account of the role of intentions in our moral appraisal of acts. Rachels tries to undermine this objection by challenging a common conception about the moral relevance of intentions. A critical examination of Rachels’ view on intentions and its bearing on his rejection of the distinction between passive and active euthanasia is worth undertaking if we are to give a proper evaluation of this most interesting debate. It is the aim of this paper to offer such an examination. Some preliminary clarifications are made in Section II. A variety of cases where futile therapy is withdrawn or withheld are not to be confused with passive euthanasia. Such a confusion can only be avoided by noting that an adequate definition of ’euthanasia’ must make clear that it is the act of bringing about a gentle death that results from the intention of one person to kill another person or to let another person die. Similarly, the correct identification of intent is crucial for the distinction between active euthanasia and some other cases of causing death in medical contexts, otherwise the argument in favor of, say, some strategies for relieving pain that unavoidably cause death stands in danger of collapsing into an argument for active euthanasia. Section III clarifies the interplay between the issue about the moral relevance of intentions and that about the distinction between killing and letting die by tracing the development of the debate between Rachels and two representative critics. Rachels’ contends that the idea that there is a moral difference between killing someone and letting someone die is mistaken can be shown by considering his example of ’Smith and Jones’. It is supposed to follow that active euthanasia is morally on a par with passive euthanasia. The AMA policy is therefore objectionable, Rachels argues, for it rests on a moral distinction between the two kinds of euthanasia. Thomas D. Sullivan and Bonnie Steinbock both accuse Rachels of misinterpreting the policy statement. In their views, the idea behind the AMA policy is not a doctrine about the distinction between active and passive euthanasia, but is simply a prohibition against intentional killing. Rachels tries to undermine this challenge by rejecting the traditional view that there is a definite sort of moral relation between act and intention. His example of ’Jack and Jill ’, he argues, shows that the accompanying intention, though relevant to assessing the character of the person who does an act, is not relevant to deciding whether the act is right or wrong. Both in launching his attack and replying to critics, Rachels relies heavily on the method of equalized cases. Sections IV starts with an analysis of the form and structure of this method, followed by an example of equalized cases (’Wong and Lee’) designed to show that Rachels’ overall position is problematic. The example does its work by having the following feature: the bare difference between the two cases is one that involves both an act/omission aspect and an intentional aspect. Committed to a ’no relevance’ -view regarding both aspects, Rachels would have to give a perverse, or highly contestable, assessment of the moral qualities of the acts in the example. This suggests that something is seriously wrong with his view. The root of the problem is that the two issues - that of the moral relevance of intentions and that of the distinction between act and omission - are subtly connected. Section V firstly addresses the problem about intentions and then sheds light on the subtlety by way of a discussion of the principle of double effect. Another pair of equalized cases (’The Two Pilots’) is introduced to show why Rachels’ view on intentions is flawed. The principle of double effect is an inconsequentialist one that recognizes the role of intentions in assessing acts. Many of our acts have both good and bad effects. This gives rise to the question of when an act of this kind is morally permissible. The principle defines that it is absolutely wrong to intentionally bring about a bad consequence but permissible to perform an action (in pursuit of a good) when the resulting harm is foreseeable but not intentionally procured. The example of ’Two Bombers’ is given as an illustration, followed by considerations of some objections concerning the individuation of action and the identification of intent. Section VI elaborates the points emerged from these considerations. First, it is suggested that (a) whether, and how much, killing differs morally from letting die in any particular case may depend on what sort of intention is involved. Second, (a) can be further supported by considering one particular kind of equalized cases involving killing and letting die, i.e., those cases commonly encountered in everyday life where the killing, but not the letting die, is accompanied by an objectionable intention. Third, holding (a) allows us to maintain that (b) intentional killing is in general worse than unintentional letting die. (b) is of unique importance because in everyday life by far most of the comparable cases where we think it is important to make a moral distinction between killing and letting die fall under the category of ’intentional-act/unintentional-omission’. Intuitively, this sort of cases of ’killing vis-a-vis letting die’ involves the greatest moral discrimination. And our common moral responses to these cases conform strongly to (b). No adequate moral view can afford to discount the intuitive force behind such conformity. Four, Rachels’ consequentialist rejection of the moral difference between killing and letting die and the moral relevance of intentions is therefore bound to strike us as most disturbing in the ’intentional-act/unintentional-omission’ type of cases. This explains why our example of ’Wong and Lee’ tends to embarrass those who hold both negative theses that Rachels has offered. His example of ’Smith and Jones’ did not strike us as particularly disturbing only because it is of a different type. In light of our analysis, one may explain Rachels’ moral assessment of the acts of Smith and Jones in terms of some kind of counteracting effect, i.e., that the moral weight of the distinction between killing and letting die is counteracted by the presence of the malicious intention shared by the two protagonists. DOWNLOAD HISTORY | This article has been downloaded 115 times in Digital Commons before migrating into this platform.